KESIAPAN BERWIRAUSAHA MAHASISWA TEKNIK MESIN SEKOLAH TINGGI TEKNIK INDUSTRI BONTANG DITINJAU DARI PENGETAHUAN KEWIRAUSAHAAN, DUKUNGAN KELUARGA, SOFT SKILL, DAN PRESTASI BELAJAR - Irianto (BEduManagers Journal : Borneo Educational Management and Research Journal, 2023)
The study aimed to investigate: (1) the influence of entrepreneurship knowledge, family support, soft skill and learning achievement on the students entrepreneurship readiness, (2) the influence of entrepreneurship knowledge on the students entrepreneurship readiness, (3) the influence of family support on the students entrepreneurship readiness, (4) the influence of soft skills on the students entrepreneurship readiness, (5) the influence of learning achievement on the students entrepreneurship readiness. The population of this research was all students of Mechanical Engineering, STTIB Bontang in the academic year of 2022/2023 who had taken the entrepreneurship course. Therefore, the subject of this research was 106 from the academic year of 2020 - 2021 The research finding follow: (1) there are influence of entrepreneurship knowledge, family support, soft skills and learning achievement on the students’ entrepreneurship readiness, (2) there are influence of entrepreneurship knowledge on the students’ entrepreneurship readiness shown by the partial correlations result, (3) there are influence of family support on the students’ entrepreneurship readiness, (4) there are influence of soft skills on the students’ entrepreneurship readiness, (5) there are influence of learning achievement on the students’ entrepreneurship readiness.